2017
DOI: 10.1007/978-1-4939-7113-8_10
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Mesenchymal-Fibroblast Cells Using the Col1a2 Promoter/Enhancer

Abstract: Excessive deposition of extracellular matrix (ECM) is a common hallmark of fibrotic diseases in various organs. Chiefly among this ECM are collagen types I and III, secreted by local fibroblasts, and other mesenchymal cells recruited for repair purposes. In the last two decades, the search for a fibroblast-specific promoter/enhancer has intensified in order to control the regulation of ECM in these cells and limit the scarring of the fibrotic process. In our previous work, we characterized an enhancer region 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Cluster 3 shows enrichment for genes associated with hemoglobin, whereas cluster 4 shows enriched expression of genes involved in immune-related processes 23,24 . Cluster 5 displays enrichment for mesenchymal genes [25][26][27] (Figure 1c, Supplementary table 1).…”
Section: Unsupervised Clustering Defines Spatial Distribution Of Exprmentioning
confidence: 99%
“…Cluster 3 shows enrichment for genes associated with hemoglobin, whereas cluster 4 shows enriched expression of genes involved in immune-related processes 23,24 . Cluster 5 displays enrichment for mesenchymal genes [25][26][27] (Figure 1c, Supplementary table 1).…”
Section: Unsupervised Clustering Defines Spatial Distribution Of Exprmentioning
confidence: 99%
“…For lineage tracing, mice hemizygous for a tamoxifendependent Cre recombinase under the control of a Col1a2 18 or Sox2 (Institut Clinique de la Souris, Alsace, France) promoter [Col1a2-Cre(ER)-T; Sox2-Cre(ER)-T] were bred with mice homozygous for a double-fluorescent reporter transgene (mTmG) integrated into the Gt(ROSA) 26Sor locus (Jackson Laboratories, Bar Harbor, ME), thereby generating Col1a2-Cre(ER)T; Rosa26mTmG or Sox2-Cre(ER)T; Rosa26mTmG mice. Please note Col1a2-Cre(ER)-T mice contain a fibroblast-specific far upstream enhancer, initially identified in the laboratory of Benoit de Crombrugghe, subcloned upstream of the Col1a2 minimal promoter; previous publications have extensively shown that this construct permits transgene expression only in fibroblasts and not in other collagen-expressing cells, such as bone and cartilage.…”
Section: Generation Of Transgenic Micementioning
confidence: 99%
“…SKP spheroids were cultured in SKP base media: three parts DMEM glutaMAX and one part Hams F12 (Invitrogen); supplemented with 1% antibiotic-antimycotic, 2% B27 (Invitrogen; A35828-01), 1% N2 (Invitrogen; 17502048), epidermal growth factor (20 ng/mL; Invitrogen; PHG0311), and basic fibroblast growth factor (20 ng/mL; Invitrogen; PHG0026). 18,19 Alternatively, to generate larger quantities of SKPs, similar to a previously described report, 20 confluent 10-cm plates of fibroblasts were removed with 0.25% trypsin (Invitrogen) and resuspended in SKP base media, as described above. Cells were then seeded into 3 wells of a 6well plate per 10-cm plate of fibroblasts.…”
Section: Cell Extraction and Culturementioning
confidence: 99%
See 2 more Smart Citations